Evaluation of the analgesic activity of the water soluble extract of stem of Tinospora cordifolia in experimentally induced pain in albino rats - ., Sumanlata; Suman, Akanksha; Sharma, Rajeev Kumar; Jindal, Meenakshi; Khan, Adnan (International Journal of Research in Medical Sciences, 2019)
Background: Pain and pyrexia are the warning signals, primarily protective in nature, that cause discomfort and suffering and may even be unbearable and incapacitating. The modern drugs (like opioids, NSAIDs, corticosteroids) currently used for the management of pain, fever and inflammatory conditions, present with many known adverse effects. Tinospora cordifolia known as Giloe, widely used in folk medicine due to its property to cure a number of diseases. Hence the present study was undertaken to explore the analgesic activity of water-soluble extract of stem of T. cordifolia in albino rats in experimentally induced pain. Methods: Present study was done in the department of pharmacology, albino rats were used to study the analgesic activity of T. cordifolia aqueous extract at the dose of 1.25g/kg,2.5g/kg and 5g/kg p.o. Various methods like Eddy’s hot plate, tail flick test and acetic acid induced writhing were used for the anti- nociceptive study. Results: In Eddy’s hot plate and tail flick test an increase in reaction time was observed with peak effect at 90min. Results were similar to the standard drug Tramadol in acetic acid induced writhing increase in time of onset, decrease in number and duration of writhing was observed. Conclusions: Aqueous extract of T. cordifolia was effective in all the three models of pain suggesting its possible action by central and peripheral mechanisms. Activity of T. cordifolia can be attributed to various phytoconstituents viz. protoberberine alkaloids, terpenoids, glycosides and polysaccharides. It can be developed as potent analgesic agent in future.